Faktor-Faktor yang Berhubungan dengan Pemberian Asi Ekslusif di Wilayah Kerja Puskesmas Naibonat Kecamatan Kupang Timur Kabupaten Kupang - Doni Aluman; Utma Aspatria; Anna Talahatu (SEHATMAS: Jurnal Ilmiah Kesehatan Masyarakat, 2025)
Breast milk is the first and main natural food for newborns. Breast milk can meet the baby's needs for energy and nutrition during the first 4-6 months of life, so that it can achieve optimal growth. To find out the factors related to exclusive breastfeeding in the working area of the Naibonat Health Center, East Kupang District, Kupang Regency. This study uses an analytical survey research design. The population in this study was 296 with a sample consisting of 119 toddlers with a proportional random sampling technique. The sampling technique is proportional random sampling, which is a sampling technique from members of the population that is carried out randomly without paying attention to the strata in the population. The collection of research data using questionnaires, this research co-investigator was adopted from the research of Sius Aryanto Zudy in 2021 (Zudy Sius Aryanto, 2022). The data was analyzed using the chi square statistical test with a significance level of α=0.05, using univariate analysis and bivariate analysis. The results of this study showed that there was a significant relationship between maternal knowledge (p=0.027)) and maternal attitudes (p=0.027) with exclusive breastfeeding while age (p=0.316), education level (p=0.235), occupation (p=0.373), family support (p=0.225) were not related to exclusive breastfeeding in the working area of the Naibonat Health Center. For the Puskesmas, it should provide counseling to the community, especially mothers to breastfeed their babies immediately after giving birth for 6 months or provide exclusive breastfeeding without other additional foods for 6 months.